W kwestii pochodzenia biskupa krakowskiego Jana Muskaty - Pietras, Tomasz (Acta Universitatis Lodziensis. Folia Historica, 2001)
The bishop of Kraków called Muskata (ca 1250-1320) represented the most eminent politicians and Church dignitaries in the break-through period of Polish re-unification after the time of provincial disintegration. He was renowned as a staunch supporter of the Polish-Czech union and was hostile to the concept of unification on the basis of the Piast dynasty, which, in turn, was represented by Władysław Łokietek. One can assume Muskata’s national, social and province origin had impact upon his future political stand. Unfortunately, there are only very few contemporary source references to Muskata, and they are sometimes contradictory - some sources point to his German origin, while others make him originate from Wrocław. We can only identify his brother Stefan and sister Adelaida, Gerlach de Culpen’s wife, while we ignore the rest of the family. Muskata’s brother-in-low’s hometown was Culpin in Holstein and his relatives can be encountered in Silesia in the XlVth century. The meaning of the bishop’s nickname is unclear. Nor is the interpretation of his coats of arms preserved in one of the seals. Having analysed Zofia Koziowska-Budkowa’s research, I have accepted her hypothesis, which connects the nickname with nutmeg-apples, which his father, Wrocław merchant, traded in. On the other hand, I have rejected the hypothesis which makes Muskata come from the knightly family of the Wierzbnowie of Muszkowice. Having made an attempt to trace Muskala’s father in the environment of Wrocław citizens I have come to the conclusion that his probable father was a town council member of German origin, probably a stall-keeper and a retailer who dealt in, among other things, nutmeg-apples. 1 have pointed to a certain Jan (before 1280), who belonged to the above mentioned Wrocław wealthy citizens’ group and was recorded in the sources of the XIIIth century. I have also concluded that Muskata was born most probably in the main market of Wrocław or in stall-keepers’ street, both of which, around the year 1250, were flanked with rich stall-keepers’ houses. The above-mentioned conclusions are confirmed by numerous facts from the resource of Muskata’s political and Church activities, and even his personal life. I am of the opinion that the presented Silesian-German origin of the bishop was one of the most important reasons for his support to this reunification concept which tended to tie Silesia and Małopolska with the Czech Kingdom. Citizens of Kraków and Wrocław also supported the same option.